2010
DOI: 10.1007/s11239-010-0450-z
|View full text |Cite
|
Sign up to set email alerts
|

Construction of thrombus-targeted microbubbles carrying tissue plasminogen activator and their in vitro thrombolysis efficacy: a primary research

Abstract: Thrombosis is the common mechanism of various diseases of heart and vasculature and their major morbility and mortality. An efficient, safe and easy thrombolysis method is needed. We tried to develop a new type of ultrasound microbubbles carrying thrombolytics and simultaneously targeting to thrombus, which could bind with thrombus specifically and release the encapsulated drug locally under the ultrasound exposure. Microbubbles carrying tissue plasminogen activator (tPA) and Arg-Gly-Asp-Ser tetrapeptide (RGDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Culp et al [200] and Xie et al [201] both demonstrated that GP IIb/IIIa targeted microbubbles exposed to US expedite lysis more than non-targeted microbubbles in vivo. Hua et al [202] demonstrated similar results in vitro using microbubbles conjugated to a tetrapeptide for targeting activated platelets. Fibrin can be targeted by conjugating an inactive portion of rt-PA to the drug delivery vesicle.…”
Section: Drug Targetingmentioning
confidence: 77%
See 1 more Smart Citation
“…Culp et al [200] and Xie et al [201] both demonstrated that GP IIb/IIIa targeted microbubbles exposed to US expedite lysis more than non-targeted microbubbles in vivo. Hua et al [202] demonstrated similar results in vitro using microbubbles conjugated to a tetrapeptide for targeting activated platelets. Fibrin can be targeted by conjugating an inactive portion of rt-PA to the drug delivery vesicle.…”
Section: Drug Targetingmentioning
confidence: 77%
“…Platelets, which exist in high concentrations on the surface of thrombi, can be targeted by conjugating a glycoprotein (GP) IIb/IIIa receptor inhibitor to the delivery vesicle [200][201][202][203][204]. Investigations implementing this targeting strategy show enhanced thrombolysis in the presence of a thrombolytic and targeted microbubbles exposed to US.…”
Section: Drug Targetingmentioning
confidence: 99%
“…Following a 50% t-Pa entrapment into eliP, ex vivo porcine clots treated with tPa-loaded echogenic liposomes were lysed with an effect similar to treatment with free t-Pa. 36 t-Pa can also be delivered as a PeGylated anionic gelatin complex 37 or in microbubbles with the arg-Gly-asp-ser (rGds) tetrapeptide as a targeting agent. 38 in both cases, after iv injection in a rabbit model, t-Pa was released from the nano-sized delivery complex when exposed to ultrasound.…”
Section: Thrombolytic Therapy With Polymeric Nanocarriers and Immunolmentioning
confidence: 90%
“…Moreover, in recent studies, plasminogen activators were encapsulated into echogenic liposomes (G. J. Shaw et al 2009) and thrombustargeted microbubbles (Hua et al 2010) whose shell is destroyed by US; such a strategy permits to further enhance the local character of the removal therapy. Potential for such combined strategies is further discussed in Section 5.…”
Section: Us-enhanced Thrombolysismentioning
confidence: 99%